Answer:
Explanation:
Slope intercept is written in the form of:
y
=
m
x
+
c
m
is the gradient of the line.
c
is the y-intercept.
You can convert the given equation to the slope intercept form by simplifying the equation and grouping the like terms. Steps are as follow:
y
+
5
=
−
6
(
x
+
7
)
Expand the bracket by multiplying
−
6
with the inner components of the bracket.
y
+
5
=
−
6
x
−
42
Subtract both sides by
5
to get '
y
' on its on.
y
=
−
6
x
−
47
and there you have it. The equation has now been converted to slope incercept form (
y
=
m
x
+
c
).